First Record of Catfish Amblyceps waikhomi (Darshan, Kachari, Dutta, Ganguly, and Das 2016) (Siluriformes: Amblycipitidae) for Nepal from the Singhiya River of Morang District, Eastern Nepal - Limbu, Jash Hang; Rajbanshi, Dipak; Subba, Bharat Raj; Subba, Asmit; Yang, Jin-Quan; Li, Chenhong (International Journal of Zoology, 2023)
In 2016, Amblyceps waikhomi from the Brahmaputra drainage of Arunachal Pradesh, India, was described. Based on morphometric and meristic characteristics, we report the first-ever sighting of A. waikhomi from the Singhiya River in Morang district. A deeper body depth at the anus sets the A. waikhomi apart from its congeners. The river systems of Nepal are home to two Amblycipitidae species, including this one.